Special protective slag to reduce the degradation rate of 304 stainless steel black belt
By using modified composite oxides in the protective slag, combining the coordination compounds of lanthanum niobium composite oxide and tributyl phosphate, the black belt problem caused by traditional protective slag is solved, and higher liquid steel purity and metals are achieved. Material properties.
Patent Information
- Application Number
- CN202411416585.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-10-11
AI Technical Summary
During the continuous casting of stainless steel, traditional protective slags have high oxide content, which can form a black belt that is difficult to remove on the surface of the billet, affecting product quality and performance.
Modified composite oxides are used as the main component of the protective slag. Through the complex oxides of lanthanum and niobium and the coordination compounds of tributyl phosphate, the oxide content is reduced, the fluidity and coverage of the protective slag are improved, and the oxidation is enhanced. adsorption capacity of inclusions.
It effectively reduces the occurrence of black belt phenomenon in the production process of stainless steel, improves the purity of the steel and the mechanical properties of metal materials, and reduces the possibility of oxide deposition.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of protective slag, in particular to a special protective slag for reducing the degradation rate of 304 stainless steel black belt. Background Art
[0002] Stainless steel materials have been widely used in aerospace, chemical, electronics, medical equipment and other fields. However, during the continuous casting process of stainless steel, due to its high temperature, high melting point, easy oxidation and other characteristics, it will cause a series of quality problems, such as poor fluidity of molten iron and severe oxidation of slab surface. In order to solve these problems, it is necessary to use protective slag and other methods to improve the quality of stainless steel materials and reduce production costs. Protective slag has the functions of isolating air, preventing molten metal from oxidizing, helping to remove non-metallic inclusions in molten metal, forming a lubricating layer between the crystallizer wall and the solidified billet shell, and reducing the resistance of billet drawing.
[0003] However, traditional protective slag cannot be completely removed during the continuous casting process due to its high oxide content, forming inclusions on the surface of the billet. These inclusions react with the steel surface during cooling to form black belts that are difficult to remove, affecting the product quality and performance in subsequent processing. In view of this, a special protective slag is provided to reduce the black belt degradation rate of 304 stainless steel. Summary of the invention
[0004] The purpose of the present invention is to provide a special protective slag for reducing the degradation rate of black belt of 304 stainless steel, so as to solve the problem that the traditional protective slag mentioned in the above background technology is prone to black belt in the stainless steel preparation process.
[0005] To achieve the above object, the present invention aims to provide a special protective slag for reducing the degradation rate of 304 stainless steel black belt, comprising the following components in parts by weight: 4-8 parts by weight of modified composite oxide, 30-40 parts by weight of calcium oxide, 20-30 parts by weight of silicon dioxide, 10-20 parts by weight of aluminum oxide, 5-12 parts by weight of magnesium oxide, 8-15 parts by weight of calcium fluoride, 3-5 parts by weight of iron oxide, 0.05-0.08 parts by weight of calcium sulfide desulfurizer, and 2-4 parts by weight of titanium dioxide flux; wherein the modified composite oxide is prepared by a sol-gel method using lanthanum nitrate and niobium oxalate in a mass ratio of 1:0.3-0.5 and then modified with tributyl phosphate.
[0006] As a further improvement of the technical solution, the specific preparation method of the modified composite oxide is as follows:
[0007] Lanthanum nitrate and niobium oxalate are dissolved in deionized water to form a mixed solution, tributyl phosphate is added to the mixed solution to obtain a mixed precursor solution, and then nitric acid is added to adjust the pH of the mixed precursor solution. The above solution is continuously stirred with a stirrer to fully mix the components, and the mixed solution is heated in a water bath at 80-100° C. until the solution becomes viscous for 3-5 hours, and then placed in an oven at 80-100° C. for drying for 1-3 hours, and the dried sample is calcined in a muffle furnace to obtain a modified composite oxide.
[0008] Lanthanum can lower the melting point of protective slag, thereby improving its fluidity and coverage, so that the protective slag can better cover the surface of molten steel, reduce the chance of molten steel contacting oxygen, increase the adsorption capacity of protective slag for oxide inclusions, help remove non-metallic inclusions in molten steel, and reduce the occurrence of black band phenomenon caused by inclusions. At the same time, lanthanum can react with oxygen in molten steel to generate stable lanthanum oxides. These oxides usually have a higher melting point and lower density, and are easy to float and be captured by protective slag, thereby reducing the possibility of oxide deposition on the surface of the billet. At the same time, rare earth elements can also be used as grain refiners, which help to refine the grain size of molten steel during crystallization, improve its microstructure, reduce the formation of pores and cracks, and improve the mechanical properties of steel. However, rare earth elements have strong reactivity and will react chemically with other components in the slag, resulting in unstable slag and difficult to control, thereby affecting its performance, or forming new inclusions, which in turn affects the mechanical properties, corrosion resistance and stability of stainless steel. Therefore, lanthanum and niobium are compositely oxidized to obtain lanthanum. Niobium composite oxide is used to improve the stability of lanthanum and protect the stability of other components. In addition, niobium can form stable carbides and nitrides with carbon and nitrogen in steel to reduce the risk of intergranular corrosion. At the same time, the addition of tributyl phosphate can provide a pair of lone pairs of electrons through phosphorus atoms to form coordination bonds with lanthanum and niobium, which can improve the solubility of metal ions in the solution, so that the precursors of lanthanum and niobium can be more evenly distributed in the solution, avoiding the aggregation of particles caused by premature precipitation, thereby obtaining a finer and more uniform particle size. Due to calcination at high temperature, in addition to forming lanthanum-niobium composite oxide, tributyl phosphate forms a coordination compound with lanthanum, which will decompose at high temperature. Lanthanum and the phosphate generated by the decomposition will recombine to form a phosphorus-containing compound, and the phosphorus in the phosphorus-containing compound can react with oxygen to form a more stable phosphate compound, reducing the oxide content. Similarly, phosphorus can also react with sulfur to form a stable sulfide or sulfur-phosphorus compound, reducing the formation of sulfide inclusions, so it can effectively reduce non-metallic inclusions in molten steel and improve the purity of metal materials.
[0009] As a further improvement of the technical solution, the mass fraction of the nitric acid is 55-65%.
[0010] As a further improvement of the technical solution, the pH value of the mixed precursor solution is 2-4.
[0011] As a further improvement of the technical solution, the mass ratio of the mixed solution to tributyl phosphate is 1:9-14.
[0012] As a further improvement of the technical solution, the calcination temperature of the muffle furnace is set to 600-800° C., and the calcination time is 4-6 hours.
[0013] As a further improvement of the technical solution, the rotation speed of the stirrer is 500-600 rpm / min, and the stirring time is 15-20 min.
[0014] As a further improvement of the technical solution, the specific preparation method of the protective slag is as follows:
[0015] The modified composite oxide, calcium oxide, silicon dioxide, aluminum oxide, magnesium oxide, calcium fluoride, iron oxide, calcium sulfide desulfurizer and titanium dioxide flux are weighed in sequence and placed in a stirrer for 15-30 minutes. After being fully stirred, the raw materials are placed in a heating furnace for heating. After the raw materials are fully melted and mixed evenly, they are poured into a mold and cooled to room temperature. The cooling rate is controlled to be 10-15°C / h, and the raw materials are crushed into particles by a crusher. The particle size of the protective slag is screened with a sieve, and the protective slag is dried and stored to obtain the protective slag.
[0016] As a further improvement of the technical solution, the heating temperature of the heating furnace is 1200-1400° C., and the heating time is 2-4 hours.
[0017] As a further improvement of the technical solution, the particle size of the protective slag screened by the screen is 0.5-0.1mm.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] In the special protective slag for reducing the black belt degradation rate of 304 stainless steel, modified composite oxides are used. Lanthanum, as a rare earth element, has a strong affinity for oxygen and can effectively form stable compounds with oxygen elements in molten steel, thereby reducing non-metallic inclusions in the molten steel and improving the purity of the molten steel. The composite oxide is prepared in combination with niobium, which reduces the chemical reaction activity of the lanthanum element and overcomes the problem that the lanthanum element is easy to react with other components in the protective slag, resulting in unstable performance of the protective slag. Tributyl phosphate is used to form a coordination compound with lanthanum to regenerate a phosphorus-containing compound at a high temperature. The phosphorus reacts with oxygen and sulfur to form a stable compound, thereby reducing the formation of inclusions, improving the purity of the metal material, and reducing the generation of black belt phenomenon in the stainless steel production process. DETAILED DESCRIPTION
[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0021] The invention discloses a special protective slag for reducing the degradation rate of 304 stainless steel black belt, comprising the following components in parts by weight: 4-8 parts by weight of modified composite oxide, 30-40 parts by weight of calcium oxide, 20-30 parts by weight of silicon dioxide, 10-20 parts by weight of aluminum oxide, 5-12 parts by weight of magnesium oxide, 8-15 parts by weight of calcium fluoride, 3-5 parts by weight of iron oxide, 0.05-0.08 parts by weight of calcium sulfide desulfurizer, and 2-4 parts by weight of titanium dioxide flux; wherein the modified composite oxide is prepared by a sol-gel method using lanthanum nitrate and niobium oxalate in a mass ratio of 1:0.3-0.5 and then modified with tributyl phosphate.
[0022] Embodiment 1: In this embodiment, the specific preparation method of the special protective slag for reducing the degradation rate of 304 stainless steel black belt is as follows:
[0023] Prepare the following components: 4g of modified composite oxide, 30g of calcium oxide, 20g of silicon dioxide, 10g of aluminum oxide, 5g of magnesium oxide, 8g of calcium fluoride, 3g of iron oxide, 0.05g of calcium sulfide desulfurizer, and 2g of titanium dioxide flux; wherein the modified composite oxide is prepared by sol-gel method with lanthanum nitrate and niobium oxalate in a mass ratio of 1:0.5 and tributyl phosphate; the mixed solution and tributyl phosphate are mixed in a mass ratio of 1:14;
[0024] Lanthanum nitrate and niobium oxalate were dissolved in 100 mL of deionized water to form a mixed solution, tributyl phosphate was added to the mixed solution to obtain a mixed precursor solution, and then 60% by mass nitric acid was added to adjust the pH of the mixed precursor solution to 4, and then stirred for 15 minutes under the stirring of a stirrer at 600 rpm / min to fully mix the components, and the mixed solution was heated in an 80°C water bath until the solution became viscous for 5 hours, and then placed in an oven at 80°C for 3 hours. The dried sample was calcined at 800°C in a muffle furnace for 4 hours to obtain a modified composite oxide.
[0025] Modified composite oxide, calcium oxide, silicon dioxide, aluminum oxide, magnesium oxide, calcium fluoride, iron oxide, calcium sulfide desulfurizer and titanium dioxide flux were weighed in turn and placed in a stirrer for 15 minutes. After being fully stirred, the raw materials were placed in a heating furnace and heated for 4 hours at a heating temperature of 1400°C. After the raw materials were fully melted and mixed evenly, they were poured into a mold and cooled to room temperature. The cooling rate was controlled at 15°C / h. The raw materials were crushed into particles with a crusher, and the protective slag was screened with a sieve to a particle size of 0.1 mm. The protective slag was dried and stored to obtain the protective slag.
[0026] Example 2: In this example, the specific preparation method of the special protective slag for reducing the degradation rate of 304 stainless steel black belt is as follows:
[0027] Prepare the following components: 6g of modified composite oxide, 30g of calcium oxide, 20g of silicon dioxide, 10g of aluminum oxide, 5g of magnesium oxide, 8g of calcium fluoride, 3g of iron oxide, 0.05g of calcium sulfide desulfurizer, and 2g of titanium dioxide flux; wherein the modified composite oxide is prepared by sol-gel method with lanthanum nitrate and niobium oxalate in a mass ratio of 1:0.5 and tributyl phosphate; the mixed solution and tributyl phosphate are mixed in a mass ratio of 1:14;
[0028] Lanthanum nitrate and niobium oxalate were dissolved in 100 mL of deionized water to form a mixed solution, tributyl phosphate was added to the mixed solution to obtain a mixed precursor solution, and then 60% by mass nitric acid was added to adjust the pH of the mixed precursor solution to 4, and then stirred for 15 minutes under the stirring of a stirrer at 600 rpm / min to fully mix the components, and the mixed solution was heated in an 80°C water bath until the solution became viscous for 5 hours, and then placed in an oven at 80°C for 3 hours. The dried sample was calcined at 800°C in a muffle furnace for 4 hours to obtain a modified composite oxide.
[0029] Modified composite oxide, calcium oxide, silicon dioxide, aluminum oxide, magnesium oxide, calcium fluoride, iron oxide, calcium sulfide desulfurizer and titanium dioxide flux were weighed in turn and placed in a stirrer for 15 minutes. After being fully stirred, the raw materials were placed in a heating furnace and heated for 4 hours at a heating temperature of 1400°C. After the raw materials were fully melted and mixed evenly, they were poured into a mold and cooled to room temperature. The cooling rate was controlled at 15°C / h. The raw materials were crushed into particles with a crusher, and the protective slag was screened with a sieve to a particle size of 0.1 mm. The protective slag was dried and stored to obtain the protective slag.
[0030] Embodiment 3: In this embodiment, the specific preparation method of the special protective slag for reducing the degradation rate of 304 stainless steel black belt is as follows:
[0031] Prepare the following components: 8g of modified composite oxide, 30g of calcium oxide, 20g of silicon dioxide, 10g of aluminum oxide, 5g of magnesium oxide, 8g of calcium fluoride, 3g of iron oxide, 0.05g of calcium sulfide desulfurizer, and 2g of titanium dioxide flux; wherein the modified composite oxide is prepared by sol-gel method with lanthanum nitrate and niobium oxalate in a mass ratio of 1:0.5 and tributyl phosphate; the mixed solution and tributyl phosphate are mixed in a mass ratio of 1:14;
[0032] Lanthanum nitrate and niobium oxalate were dissolved in 100 mL of deionized water to form a mixed solution, tributyl phosphate was added to the mixed solution to obtain a mixed precursor solution, and then 60% by mass nitric acid was added to adjust the pH of the mixed precursor solution to 4, and then stirred for 15 minutes under the stirring of a stirrer at 600 rpm / min to fully mix the components, and the mixed solution was heated in an 80°C water bath until the solution became viscous for 5 hours, and then placed in an oven at 80°C for 3 hours. The dried sample was calcined at 800°C in a muffle furnace for 4 hours to obtain a modified composite oxide.
[0033] Modified composite oxide, calcium oxide, silicon dioxide, aluminum oxide, magnesium oxide, calcium fluoride, iron oxide, calcium sulfide desulfurizer and titanium dioxide flux were weighed in turn and placed in a stirrer for 15 minutes. After being fully stirred, the raw materials were placed in a heating furnace and heated for 4 hours at a heating temperature of 1400°C. After the raw materials were fully melted and mixed evenly, they were poured into a mold and cooled to room temperature. The cooling rate was controlled at 15°C / h. The raw materials were crushed into particles with a crusher, and the protective slag was screened with a sieve to a particle size of 0.1 mm. The protective slag was dried and stored to obtain the protective slag.
[0034] Embodiment 4: In this embodiment, the specific preparation method of the special protective slag for reducing the degradation rate of 304 stainless steel black belt is as follows:
[0035] Prepare the following components: 6g of modified composite oxide, 40g of calcium oxide, 30g of silicon dioxide, 20g of aluminum oxide, 12g of magnesium oxide, 15g of calcium fluoride, 5g of iron oxide, 0.08g of calcium sulfide desulfurizer, and 4g of titanium dioxide flux; wherein the modified composite oxide is prepared by sol-gel method with lanthanum nitrate and niobium oxalate in a mass ratio of 1:0.5 and tributyl phosphate; the mixed solution and tributyl phosphate are mixed in a mass ratio of 1:14;
[0036] Lanthanum nitrate and niobium oxalate were dissolved in 100 mL of deionized water to form a mixed solution, tributyl phosphate was added to the mixed solution to obtain a mixed precursor solution, and then 60% by mass nitric acid was added to adjust the pH of the mixed precursor solution to 4, and then stirred for 15 minutes under the stirring of a stirrer at 600 rpm / min to fully mix the components, and the mixed solution was heated in an 80°C water bath until the solution became viscous for 5 hours, and then placed in an oven at 80°C for 3 hours. The dried sample was calcined at 800°C in a muffle furnace for 4 hours to obtain a modified composite oxide.
[0037] Modified composite oxide, calcium oxide, silicon dioxide, aluminum oxide, magnesium oxide, calcium fluoride, iron oxide, calcium sulfide desulfurizer and titanium dioxide flux were weighed in turn and placed in a stirrer for 15 minutes. After being fully stirred, the raw materials were placed in a heating furnace and heated for 4 hours at a heating temperature of 1400°C. After the raw materials were fully melted and mixed evenly, they were poured into a mold and cooled to room temperature. The cooling rate was controlled at 15°C / h. The raw materials were crushed into particles with a crusher, and the protective slag was screened with a sieve to a particle size of 0.1 mm. The protective slag was dried and stored to obtain the protective slag.
[0038] Embodiment 5: In this embodiment, the specific preparation method of the special protective slag for reducing the degradation rate of 304 stainless steel black belt is as follows:
[0039] Prepare the following components: 6g of modified composite oxide, 30g of calcium oxide, 20g of silicon dioxide, 10g of aluminum oxide, 5g of magnesium oxide, 8g of calcium fluoride, 3g of iron oxide, 0.05g of calcium sulfide desulfurizer, and 2g of titanium dioxide flux; wherein the modified composite oxide is prepared by sol-gel method with lanthanum nitrate and niobium oxalate in a mass ratio of 1:0.4 and tributyl phosphate; the mixed solution and tributyl phosphate are mixed in a mass ratio of 1:12;
[0040] Lanthanum nitrate and niobium oxalate were dissolved in 100 mL of deionized water to form a mixed solution, tributyl phosphate was added to the mixed solution to obtain a mixed precursor solution, and then 60% by mass nitric acid was added to adjust the pH of the mixed precursor solution to 4, and then stirred for 15 minutes under the stirring of a stirrer at 600 rpm / min to fully mix the components, and the mixed solution was heated in an 80°C water bath until the solution became viscous for 5 hours, and then placed in an oven at 80°C for 3 hours. The dried sample was calcined at 800°C in a muffle furnace for 4 hours to obtain a modified composite oxide.
[0041] Modified composite oxide, calcium oxide, silicon dioxide, aluminum oxide, magnesium oxide, calcium fluoride, iron oxide, calcium sulfide desulfurizer and titanium dioxide flux were weighed in turn and placed in a stirrer for 15 minutes. After being fully stirred, the raw materials were placed in a heating furnace and heated for 4 hours at a heating temperature of 1400°C. After the raw materials were fully melted and mixed evenly, they were poured into a mold and cooled to room temperature. The cooling rate was controlled at 15°C / h. The raw materials were crushed into particles with a crusher, and the protective slag was screened with a sieve to a particle size of 0.1 mm. The protective slag was dried and stored to obtain the protective slag.
[0042] Embodiment 6: In this embodiment, the specific preparation method of the special protective slag for reducing the degradation rate of 304 stainless steel black belt is as follows:
[0043] Prepare the following components: 6g of modified composite oxide, 30g of calcium oxide, 20g of silicon dioxide, 10g of aluminum oxide, 5g of magnesium oxide, 8g of calcium fluoride, 3g of iron oxide, 0.05g of calcium sulfide desulfurizer, and 2g of titanium dioxide flux; wherein the modified composite oxide is prepared by sol-gel method with lanthanum nitrate and niobium oxalate in a mass ratio of 1:0.3 and tributyl phosphate; the mixed solution and tributyl phosphate are mixed in a mass ratio of 1:9;
[0044] Lanthanum nitrate and niobium oxalate were dissolved in 100 mL of deionized water to form a mixed solution, tributyl phosphate was added to the mixed solution to obtain a mixed precursor solution, and then 60% by mass nitric acid was added to adjust the pH of the mixed precursor solution to 4, and then stirred for 15 minutes under the stirring of a stirrer at 600 rpm / min to fully mix the components, and the mixed solution was heated in an 80°C water bath until the solution became viscous for 5 hours, and then placed in an oven at 80°C for 3 hours. The dried sample was calcined at 800°C in a muffle furnace for 4 hours to obtain a modified composite oxide.
[0045] Modified composite oxide, calcium oxide, silicon dioxide, aluminum oxide, magnesium oxide, calcium fluoride, iron oxide, calcium sulfide desulfurizer and titanium dioxide flux were weighed in turn and placed in a stirrer for 15 minutes. After being fully stirred, the raw materials were placed in a heating furnace and heated for 4 hours at a heating temperature of 1400°C. After the raw materials were fully melted and mixed evenly, they were poured into a mold and cooled to room temperature. The cooling rate was controlled at 15°C / h. The raw materials were crushed into particles with a crusher, and the protective slag was screened with a sieve to a particle size of 0.1 mm. The protective slag was dried and stored to obtain the protective slag.
[0046] Comparative Example 1: The method of Example 2 was adopted without adding modified composite oxide.
[0047] Comparative Example 2: The method of Example 2 was adopted, lanthanum was directly added to the protective slag without mixing with niobium, and tributyl phosphate was not used.
[0048] Comparative Example 3: The method of Example 2 was adopted, and lanthanum-niobium composite oxide was added to the protective slag, but tributyl phosphate was not added.
[0049] The present invention prepares a special protective slag for reducing the degradation rate of black belt of 304 stainless steel. In the application of protective slag technology, the generation of black belt phenomenon can be effectively reduced. The specific detection is shown in the following table:
[0050] The black band degradation rate refers to the phenomenon that black stripes or spots appear on the surface of stainless steel due to various factors during the continuous casting process. This black band is usually formed on the steel surface due to the failure to effectively remove inclusions. In order to evaluate the degree of black bands, the following test method is used: use cutting equipment to cut the continuous casting billet into a size of 100mm×100mm, polish the surface of the slice to remove the oxide layer and rough parts on the surface, pickle the polished surface, use a magnifying glass to observe the sample surface in detail, record the number, size, shape and other characteristics of the black bands, use image analysis software to measure the area of the black bands, calculate the total area of the sample, and calculate the black band degradation rate using the formula, black band degradation rate = (total area of black bands / total area of samples) × 100%.
[0051] The obtained data are shown in Table 1:
[0052] Table 1 Performance data of mold slag prepared in Examples 1-6 and Comparative Examples 1-3
[0053]
[0054] By comparing Examples 1-6 with Comparative Examples 1-3, it can be seen that the special protective slag for reducing the black belt degradation rate of 304 stainless steel has a significant effect on the occurrence of the black belt phenomenon.
[0055] According to Examples 1-3, it can be seen that as the content of the modified composite oxide component continues to increase, the black band degradation first decreases and then increases. This is because the modified composite oxide can improve the oxidation resistance of the slag, reduce the free oxygen content in the slag, reduce the generation of oxides, and react with oxygen and sulfur to form stable compounds, reduce the formation of inclusions, and help reduce the formation of stainless steel black bands. When the content is too little, the beneficial effect of the modified composite oxide is not enough to significantly reduce the formation of black bands. When the content is too high, the modified composite oxide will react with other components in the molten steel or protective slag to generate new inclusions, which in turn increases the generation of black bands.
[0056] According to Example 2 and Example 4, it can be seen that with the change of the content of other components in the protective slag, the black band degradation rate has almost no obvious change. This is because the modified composite oxide is the main factor in reducing the occurrence of the black band phenomenon. Therefore, the change of the content of other components in the protective slag within a certain range will not have a significant effect on the occurrence of the black band phenomenon.
[0057] According to Example 2, Example 5 and Example 6, it can be known that as the ratio of lanthanum nitrate, niobium oxalate and tributyl phosphate in the modified composite oxide continues to change, the black band degradation rate continues to change. This is because lanthanum can lower the melting point of the protective slag, improve its fluidity and coverage, increase the adsorption capacity of the protective slag for oxide inclusions, help remove non-metallic inclusions in the molten steel, and can also be used as a grain refiner to help refine the grain size of the molten steel during crystallization. Niobium can form stable carbides and nitrides with carbon and nitrogen in the steel to reduce the risk of intergranular corrosion. Phosphorus can react with sulfur to form more stable sulfur compounds and reduce the formation of sulfide inclusions. Therefore, when its content decreases, the occurrence of the black band phenomenon increases.
[0058] According to the above test experiments, Example 2 is used as the optimal example and compared with Comparative Examples 1-3 respectively.
[0059] By comparing Example 2 and Comparative Example 1, it can be seen that the black band degradation rate is worse when no modified composite oxide is added. This is because the modified composite oxide can improve the fluidity of the slag, reduce the viscosity of the slag, help to float and remove inclusions in the molten steel, improve the oxidation resistance of the slag, reduce the formation of oxides, and react with oxygen and sulfur to form stable compounds, reduce the formation of inclusions, and thus reduce the formation of black bands. Therefore, in the absence of modified composite oxides, the performance of the protective slag is relatively poor, resulting in a higher black band degradation rate.
[0060] By comparing Example 2 with Comparative Example 2, it can be seen that when lanthanum is directly added to the protective slag without mixing with niobium and without using tributyl phosphate, the black belt degradation rate is worse. This is because lanthanum has a high reactivity and will react with other components in the protective slag, causing the stability of the protective slag to deteriorate or form new inclusions, thereby affecting the quality of the stainless steel, and the black belt degradation rate is worse.
[0061] By comparing Example 2 and Comparative Example 3, it can be seen that the black belt degradation rate is worse when lanthanum-niobium composite oxide is added to the protective slag but tributyl phosphate is not added. This is because the use of tributyl phosphate can not only increase the solubility of metal ions in the solution, but also form phosphorus-containing compounds with lanthanum, react with oxygen and sulfur to form stable compounds, reduce the formation of inclusions, and thus reduce the formation of black belts. Therefore, tributyl phosphate is needed for modification.
[0062] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments, and the above embodiments and descriptions are only preferred examples of the present invention, and are not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.
Claims
1. A special protective slag for reducing the degradation rate of 304 stainless steel black belt, characterized by: The invention comprises the following components in parts by weight: 4-8 parts by weight of modified composite oxide, 30-40 parts by weight of calcium oxide, 20-30 parts by weight of silicon dioxide, 10-20 parts by weight of aluminum oxide, 5-12 parts by weight of magnesium oxide, 8-15 parts by weight of calcium fluoride, 3-5 parts by weight of iron oxide, 0.05-0.08 parts by weight of calcium sulfide desulfurizer, and 2-4 parts by weight of titanium dioxide flux; The modified composite oxide is prepared by a sol-gel method using lanthanum nitrate and niobium oxalate in a mass ratio of 1:0.3-0.5 and tributyl phosphate, and then modified.
2. The special protective slag for reducing the degradation rate of 304 stainless steel black belt according to claim 1, characterized in that: The specific preparation method of the modified composite oxide is as follows: Lanthanum nitrate and niobium oxalate are dissolved in deionized water to form a mixed solution, tributyl phosphate is added to the mixed solution to obtain a mixed precursor solution, and then nitric acid is added to adjust the pH of the mixed precursor solution. The above solution is continuously stirred with a stirrer to fully mix the components, and the mixed solution is heated in a water bath at 80-100° C. until the solution becomes viscous for 3-5 hours, and then placed in an oven at 80-100° C. for drying for 1-3 hours, and the dried sample is calcined in a muffle furnace to obtain a modified composite oxide.
3. The special protective slag for reducing the degradation rate of 304 stainless steel black belt according to claim 2, characterized in that: The mass fraction of the nitric acid is 55-65%.
4. The special protective slag for reducing the degradation rate of 304 stainless steel black belt according to claim 2, characterized in that: The pH value of the mixed precursor solution is 2-4.
5. The special protective slag for reducing the degradation rate of 304 stainless steel black belt according to claim 2, characterized in that: The mass ratio of the mixed solution to tributyl phosphate is 1:9-14.
6. The special protective slag for reducing the degradation rate of 304 stainless steel black belt according to claim 2, characterized in that: The calcination temperature of the muffle furnace is set to 600-800° C., and the calcination time is 4-6 hours.
7. The special protective slag for reducing the degradation rate of 304 stainless steel black belt according to claim 2, characterized in that: The rotation speed of the stirrer is 500-600 rpm / min, and the stirring time is 15-20 min.
8. The special protective slag for reducing the degradation rate of 304 stainless steel black belt according to claim 1, characterized in that: The specific preparation method of the protective slag is as follows: The modified composite oxide, calcium oxide, silicon dioxide, aluminum oxide, magnesium oxide, calcium fluoride, iron oxide, calcium sulfide desulfurizer and titanium dioxide flux are weighed in sequence and placed in a stirrer for 15-30 minutes. After being fully stirred, the raw materials are placed in a heating furnace for heating. After the raw materials are fully melted and mixed evenly, they are poured into a mold and cooled to room temperature. The cooling rate is controlled to be 10-15°C / h, and the raw materials are crushed into particles by a crusher. The particle size of the protective slag is screened with a sieve, and the protective slag is dried and stored to obtain the protective slag.
9. The special protective slag for reducing the degradation rate of 304 stainless steel black belt according to claim 8, characterized in that: The heating temperature of the heating furnace is 1200-1400° C., and the heating time is 2-4 hours.
10. The special protective slag for reducing the degradation rate of 304 stainless steel black belt according to claim 8, characterized in that: The screen screens the protective slag to a particle size of 0.5-0.1 mm.
Citation Information
Patent Citations
Continuous casting protective slag for high-boron steel
CN105935750A
Casting powder for overcoming scale defect of 201 stainless steel wire
CN117943516A